Method for preparing modified lithium iron phosphate through carbon-coated metal doping and positive electrode lithium supplementation

By using carbon coating and metal doping technology in the lithium iron phosphate positive electrode material and combining the positive electrode to supplement lithium, the material conductivity and lithium ion diffusion problems are solved, the energy density and cycle life of the battery are significantly improved, and the lithium battery is reduced. Polarization phenomenon.

CN119133390APending Publication Date: 2024-12-13JIANGSU RONGHUI GENERAL LITHIUM IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411234552.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The conductivity difference and the low lithium ion diffusion coefficient of lithium iron phosphate cathode material limit their wider application. At the same time, the solid electrolyte interface phase cycle process during the first charging and discharging process leads to continuous loss of active lithium, reducing the battery reversible capacity and cycle life.

Method used

Using carbon-coated metal doping and positive electrode lithium supplementation methods, water-soluble starch as carbon source, nano-TiO2 as metal ion dopant and Li2C2O4 as lithium supplementation agent, to prepare modified lithium iron phosphate positive electrode material to improve its conductivity and cycle life.

Benefits of technology

It improves the conductivity and energy density of the electrode material, extends the cycle life of the battery, reduces the polarization phenomenon of lithium batteries, and maintains strong response capabilities under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133390A_ABST
    Figure CN119133390A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of lithium iron phosphate positive electrode materials, and discloses a method for preparing modified lithium iron phosphate through carbon-coated metal doping and positive electrode lithium supplementation, which comprises the following steps: S1, dissolving Li3PO4 powder, adding a Fe2SO. 7H2O aqueous solution into the solution, stirring and drying to obtain a LiFePO4 precursor; s2, testing the element content of the precursor; s3, supplementing a lithium source and a phosphorus source to the precursor, adding a carbon source and metal salt, and uniformly mixing; s4, the precursor mixed solution is put into a sand mill to be subjected to sand milling for 60-120 min to be fully mixed; s5, performing spray drying on the sanded precursor, and collecting a product; and S6, calcining and carbonizing the product to obtain the active substance. S7, dissolving the active substance, and magnetically stirring and mixing; and S8, performing coating and vacuum drying on the mixed slurry, and performing half-cell manufacturing and electrochemical performance testing. The crystal stability is improved, and the battery life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium iron phosphate positive electrode material preparation, and in particular to a method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation. Background Art

[0002] With the continuous development of social economy, people's energy consumption and demand are increasing. How to find a new type of green energy that is pollution-free and high-efficiency is the goal of mankind. Since its discovery, LiFePO4, a phosphate cathode material with an olivine structure, has been considered to be a promising new generation of green cathode materials due to its high theoretical specific capacity (170 mAh / g at room temperature), good thermal stability, stable voltage platform, wide source of raw materials, low price, and environmental friendliness. However, the poor conductivity and low lithium ion diffusion coefficient of olivine-type LiFePO4 cathode materials limit the wider application of LiFePO4 materials. By reviewing a large number of literatures to modify the performance defects of LiFePO4 (low conductivity and low ion diffusion coefficient), the methods are summarized and divided into three categories: 1) Surface modification of LiFePO4, by coating carbon materials such as biomass carbon materials and two-dimensional materials such as graphene to improve its conductivity; 2) Doping of LiFePO4, by doping metal elements Ni 2+ 、Co 2+ , Mn 2+ 、Al 3+ 、Ti 4+ And non-metallic elements Cl-, F-, S 2- , B 3+ etc. to improve its electrochemical performance; 3) reduce the particle size of LiFePO4 to submicron or nanometer level, or improve its electrochemical performance by preparing LiFePO4 with special morphology. The above modification methods can be used to modify the positive electrode material to improve its electronic conductivity and Li+ diffusion rate, which will guide the development of this field.

[0003] LiFePO4 battery is an ideal cathode material for lithium-ion batteries. However, the solid electrolyte interface (SEI) formed during the first charge and discharge process and the regeneration of SEI during the cycle lead to the continuous loss of active lithium, which reduces the reversible capacity of the battery and shortens the cycle life of the battery. The pre-lithiation of the cathode material is an effective way to make up for the loss, and the first charge and discharge efficiency, cycle life and energy density of the battery can be improved by replenishing lithium in the cathode.

[0004] Therefore, developing a carbon-coated, metal-doped and positive-electrode lithium supplemented method for preparing lithium iron phosphate positive electrode materials, thereby improving the energy density and cycle life of the positive electrode materials, is of great significance for the development and utilization of lithium iron phosphate positive electrode materials.

[0005] The relevant reference CN114551823A discloses a method for preparing a metal-doped carbon in-situ coated lithium iron phosphate electrode material, in which a LiFePO4 compound is mixed with a metal salt and an organic ligand, wherein the metal salt is any one or more of Cu, Zn, Ni, Co, Fe, Mn, Zr, Ti, Al, Sn, Mo, V, and Ce salts; and the organic ligand is any one or more of a carboxylic acid, a nitrogen-containing heterocyclic, and a nitrogen-oxygen mixed ligand. It cannot extend the battery life. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation, which can improve crystal stability and extend battery life.

[0007] In order to solve the above technical problems, the present invention provides a method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation, comprising the following steps: S1. Dissolve Li3PO4 powder in deionized water and perform ultrasonic dispersion, reflux heating, add Fe2SO·7H2O aqueous solution to the solution, reflux stirring, collect the product by centrifugation, and vacuum dry to obtain LiFePO4 precursor; S2. Conduct element content test on LiFePO4 precursor to determine the content of Li, Fe and P therein; S3. In order to make the ratio of nFe / nP in LiFePO4 meet 0.95-0.99 and the ratio of nLi / nFe meet 1.01-1.05, it is necessary to supplement the precursor with lithium source (Li2C2O4) and phosphorus source (H3PO4), add Li2C2O4 and H3PO4 into deionized water for ultrasonic dispersion, and add a certain amount of carbon source (water-soluble starch) as carbon coating and metal salt (nano-TiO2) as metal doping, and add LiFePO4 precursor after ultrasonic stirring. The metal mass is 0.2wt%~2wt% of the total mass, the carbon content is 0.5wt%~2wt% of the total mass, the solid-liquid ratio is controlled at 20%~50%, and ultrasonic stirring is continued to mix evenly; S4, putting the LiFePO4 precursor mixed solution into a sand mill and sand milling for 60-120 min to fully mix and refine the particles. When the sand milling is about to end, add deionized water to control the solid-liquid ratio to 6%-12%; S5, spray drying the sand-milled LiFePO4 precursor and collecting the product; S6. The spray-dried product is calcined and carbonized at a heating rate of 2-8°C / min and a calcination temperature of 650-750°C for 6-8 hours to obtain a LiFePO4 active material.

[0008] S7, dissolving the calcined active material, conductive agent (carbon black), and binder (PVDF) in NMP at a mass ratio of 9:0.5:0.5, and fully mixing them by magnetic stirring for 4-8 hours; S8. The mixed slurry is coated and vacuum dried, and finally a half-cell is fabricated and the electrochemical performance is tested.

[0009] Preferably, in step S3, the ratio of nFe / nP is 0.96, and the ratio of nLi / nFe is 1.034.

[0010] Preferably, in step S3, 4.25-4.5 g of water-soluble starch, 0.32 g of nano-TiO2, and 36 g of LiFePO4 precursor are dissolved in 100 mL of deionized water.

[0011] Preferably, in step S4, the sanding time is 90 minutes.

[0012] Preferably, in step S4, the solid-liquid ratio is controlled at 8%.

[0013] Preferably, in step S6, the heating rate is increased to 150°C at 6°C / min and kept warm for 1 hour, then increased to 450°C / min at 5°C / min and kept warm for 1 hour, and finally increased to 675°C-700°C at 2.5°C / min and kept warm for 6 hours.

[0014] Preferably, in step S7, the magnetic stirring time is 8 hours.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses water-soluble starch as a carbon source for carbon coating, nano-TiO2 as a metal ion for lithium doping, and Li2C2O4 as a lithium supplement agent for additional lithium supplementation, so as to prepare a lithium iron phosphate positive electrode material with high energy density and stable cycle life. The preparation method is simple in steps, and the raw material and process costs are green and low. The prepared electrode material has the characteristics of strong conductivity, high energy density, stable structure, strong response ability under high current density, etc.

[0016] 2. The additional lithium source (lithium oxalate) provided by the present invention makes nLi / nFe=1.034 compared with nLi / nFe=1. An appropriate excess helps to refine the particles and alleviate the sintering and fusion between particles. At the same time, lithium oxalate as a lithium supplement can improve the battery ion conductivity, improve the crystal stability and extend the battery life, while improving the initial charge and discharge efficiency and reducing the polarization phenomenon of the lithium battery.

[0017] 3. The present invention uses metal ions (TiO2) to dope lithium sites. Lithium doping can cause lattice defects in LiFePO4, which is beneficial to the diffusion of lithium ions. At the same time, during the charging and discharging process, lithium iron phosphate crystals are converted between p-type and n-type semiconductors, resulting in Fe 3+ / Fe 2+ The ratio changes, thereby improving the morphology of LiFePO4 and effectively improving the conductivity of LiFePO4. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the charge and discharge rate performance diagram at different current densities. DETAILED DESCRIPTION

[0019] In order to more clearly explain the purpose, technical solution and advantages of the embodiments of the present invention, the following will combine the embodiments of the present invention to clearly and completely describe its technical solution. Obviously, the described embodiments are only some embodiments of the present invention, not all. Figure 1 The following embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Example

[0020] Li3PO4 powder was dissolved in deionized water and ultrasonically dispersed, refluxed and heated, and Fe2SO·7H2O aqueous solution was added to the solution, refluxed and stirred, the product was collected by centrifugation, and vacuum dried to obtain LiFePO4 precursor, the molar ratio of Li, Fe, and P in the precursor was 1:1:1, and no additional lithium source was added. 4.25g of water-soluble starch and 0.32g of nano-TiO2 were added to 100mL of deionized water, ultrasonically stirred and then 36g of LiFePO4 precursor was added, and ultrasonic stirring was continued to disperse evenly.

[0021] The LiFePO4 precursor mixed solution was placed in a sand mill and sand-milled for 90 min to fully mix and refine the particles. 400 mL of deionized water was added at the end of the last 10 min of sand-milling, and the sand-milled LiFePO4 precursor was spray-dried to collect the product.

[0022] The spray-dried product was calcined and carbonized, and the temperature was increased to 150°C at 5°C / min in a nitrogen atmosphere and kept for 1 hour, then increased to 450°C / min at 5°C / min and kept for 1 hour, and finally increased to 675°C at 2.5°C / min and kept for 6 hours, and then cooled to obtain LiFePO4 active material.

[0023] The calcined active material, conductive agent (carbon black) and binder (PVDF) were dissolved in NMP at a mass ratio of 9:0.5:0.5, mixed by magnetic stirring for 8 hours, and the mixed slurry was coated and vacuum dried. Finally, half-cell production and electrochemical performance testing were carried out. Example

[0024] Li3PO4 powder was dissolved in deionized water and ultrasonically dispersed, and refluxed and heated. At the same time, Fe2SO·7H2O aqueous solution was added to the solution, refluxed and stirred, and the product was collected by centrifugation and vacuum dried to obtain LiFePO4 precursor. The contents of Li, Fe and P in the LiFePO4 precursor were tested, and the contents of Li, Fe and P were 3.99%, 32.77% and 18.53%, respectively.

[0025] In order to make the nFe / nP ratio meet 0.96 and the nLi / nFe ratio meet 1.034, 0.58g Li2C2O4 and 0.53g H3PO4 were added to 100mL deionized water for ultrasonic dispersion, and 4.25g water-soluble starch and 0.32g nano-TiO2 were added at the same time. After ultrasonic stirring, 36g LiFePO4 precursor was added and ultrasonic stirring was continued to disperse evenly.

[0026] The LiFePO4 precursor mixed solution was placed in a sand mill and sand-milled for 90 min to fully mix and refine the particles. 400 mL of deionized water was added at the end of the last 10 min of sand-milling, and the sand-milled LiFePO4 precursor was spray-dried to collect the product.

[0027] The spray-dried product was calcined and carbonized, and the temperature was increased to 150°C at 5°C / min in a nitrogen atmosphere and kept for 1 hour, then increased to 450°C / min at 5°C / min and kept for 1 hour, and finally increased to 675°C at 2.5°C / min and kept for 6 hours, and then cooled to obtain LiFePO4 active material.

[0028] The calcined active material, conductive agent (carbon black) and binder (PVDF) were dissolved in NMP at a mass ratio of 9:0.5:0.5, mixed by magnetic stirring for 8 hours, and the mixed slurry was coated and vacuum dried. Finally, half-cell production and electrochemical performance testing were carried out. Example

[0029] Li3PO4 powder was dissolved in deionized water and ultrasonically dispersed, and refluxed and heated. At the same time, Fe2SO·7H2O aqueous solution was added to the solution, refluxed and stirred, and the product was collected by centrifugation and vacuum dried to obtain LiFePO4 precursor. The contents of Li, Fe and P in the LiFePO4 precursor were tested, and the contents of Li, Fe and P were 3.99%, 32.77% and 18.53%, respectively.

[0030] In order to make the nFe / nP ratio meet 0.96 and the nLi / nFe ratio meet 1.034, 0.58g Li2C2O4 and 0.53g H3PO4 were added to 100mL deionized water for ultrasonic dispersion, and 4.5g water-soluble starch and 0.32g nano-TiO2 were added at the same time. After ultrasonic stirring, 36g LiFePO4 precursor was added and ultrasonic stirring was continued to disperse evenly.

[0031] The LiFePO4 precursor mixed solution was placed in a sand mill and sand-milled for 90 min to fully mix and refine the particles. 400 mL of deionized water was added at the end of the last 10 min of sand-milling, and the sand-milled LiFePO4 precursor was spray-dried to collect the product.

[0032] The spray-dried product was calcined and carbonized, and the temperature was increased to 150°C at 5°C / min in a nitrogen atmosphere and kept for 1 hour, then increased to 450°C / min at 5°C / min and kept for 1 hour, and finally increased to 675°C at 2.5°C / min and kept for 6 hours, and then cooled to obtain LiFePO4 active material.

[0033] The calcined active material, conductive agent (carbon black) and binder (PVDF) were dissolved in NMP at a mass ratio of 9:0.5:0.5, mixed by magnetic stirring for 8 hours, and the mixed slurry was coated and vacuum dried. Finally, half-cell production and electrochemical performance testing were carried out. Example

[0034] Li3PO4 powder was dissolved in deionized water and ultrasonically dispersed, and refluxed and heated. At the same time, Fe2SO·7H2O aqueous solution was added to the solution, refluxed and stirred, and the product was collected by centrifugation and vacuum dried to obtain LiFePO4 precursor. The contents of Li, Fe and P in the LiFePO4 precursor were tested, and the contents of Li, Fe and P were 3.99%, 32.77% and 18.53%, respectively.

[0035] In order to make the nFe / nP ratio meet 0.96 and the nLi / nFe ratio meet 1.034, 0.58g Li2C2O4 and 0.53g H3PO4 were added to 100mL deionized water for ultrasonic dispersion, and 4.5g water-soluble starch and 0.32g nano-TiO2 were added at the same time. After ultrasonic stirring, 36g LiFePO4 precursor was added and ultrasonic stirring was continued to disperse evenly.

[0036] The LiFePO4 precursor mixed solution was placed in a sand mill and sand-milled for 90 min to fully mix and refine the particles. 400 mL of deionized water was added at the end of the last 10 min of sand-milling, and the sand-milled LiFePO4 precursor was spray-dried to collect the product.

[0037] The spray-dried product was calcined and carbonized, and the temperature was increased to 150°C at 5°C / min in a nitrogen atmosphere and kept for 1 hour, then increased to 450°C / min at 5°C / min and kept for 1 hour, and finally increased to 700°C at 2.5°C / min and kept for 6 hours, and then cooled to obtain LiFePO4 active material.

[0038] The calcined active material, conductive agent (carbon black) and binder (PVDF) were dissolved in NMP at a mass ratio of 9:0.5:0.5, mixed by magnetic stirring for 8 hours, and the mixed slurry was coated and vacuum dried. Finally, half-cell production and electrochemical performance testing were carried out.

[0039] The results obtained are the specific capacity test results in the following table:

[0040] From Table 1, it can be seen that under 0.1C charge and discharge conditions, Example 1 (LFP1) is simply carbon-coated and metal-doped, and its first-cycle specific capacity and charge and discharge efficiency are low. On this basis, Examples 2, 3, and 4 add additional lithium sources to help improve the first-cycle specific capacity and first-cycle charge and discharge efficiency. That is, under 0.1C, the discharge specific capacities of Example 1 (LFP1), Example 2 (LFP2), Example 3 (LFP3), and Example 4 (LFP4) are 154.13, 159.68, 157.55, and 156.89 mAh / g. Figure 1 It can be seen that at 10C, the specific capacities of LFP1, LFP2, LFP3, and LFP4 are 92.31, 99.58, 94.36, and 93.51 mAh / g, respectively, all of which have high rate performance. This is due to the fact that carbon coating improves the conductivity of the electrode material, while titanium doping can also improve the conductivity. An appropriate amount of lithium supplementation helps to refine the particles, alleviate the sintering and fusion between particles, improve the electrochemical performance, and effectively prevent the capacity loss caused by the SEI film formed during the first charge and discharge.

[0041] As the current density increases, the battery capacity decreases. This is because the polarization of the electrode increases when the current increases. Compared with LFP1, the polarization of other electrode materials with additional lithium sources added is improved.

[0042] By comparing Example 2 and Example 3, it can be seen that at the same carbonization temperature, Example 3 adds more carbon source, and the battery capacity is reduced compared to Example 2, indicating that under the condition of coating a certain carbon content, the conductivity is effectively improved, thereby improving the charge and discharge performance, but too high a carbon content will block the lithium ion diffusion channel and reduce the specific capacity of the composite material. By comparing Example 3 and Example 4, when other conditions are the same, Example 4 has a higher carbonization temperature, which will cause the particles to agglomerate and agglomerate, and will also cause more carbon to be lost, thereby affecting the electrochemical performance.

[0043] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation, It is characterized in that The following steps are involved: S1. Li 3 PO 4 The powder was dissolved in deionized water and ultrasonically dispersed, heated under reflux, and Fe was added to the solution. 2 SO·7H 2 O aqueous solution, reflux and stir, collect the product by centrifugation, and dry in vacuum to obtain LiFePO 4 Precursor; S2, LiFePO 4 The precursor is tested for element content to determine the content of Li, Fe, and P; S3, in order to make LiFePO 4 The ratio of nFe / nP in the reaction mixture is 0.95-0.99, and the ratio of nLi / nFe in the reaction mixture is 1.01-1.

05. 2 C 2 O 4 ) and phosphorus source (H 3 PO 4 ), will Li 2 C 2 O 4 and H 3 PO 4 Add deionized water for ultrasonic dispersion, and add a certain amount of carbon source (water-soluble starch) as carbon coating and metal salt (nano-TiO 2 ) as metal doping, and LiFePO was added after ultrasonic stirring. 4 Precursor, metal mass is 0.2wt%~2wt% of the total mass, carbon content is 0.5wt%~2wt% of the total mass, solid-liquid ratio is controlled at 20%~50%, and ultrasonic stirring is continued to mix evenly; S4, LiFePO 4 The precursor mixed solution was placed in a sand mill and sand-milled for 60-120 min to fully mix and refine the particles. Deionized water was added at the end of the sand milling to control the solid-liquid ratio to 6%-12%; S5, the sanded LiFePO 4 The precursor is spray dried and the product is collected; S6, calcining and carbonizing the spray-dried product at a heating rate of 2-8°C / min, calcining at 650-750°C for 6-8 hours to obtain LiFePO 4 Active substances; S7, dissolving the calcined active material, conductive agent (carbon black), and binder (PVDF) in NMP at a mass ratio of 9:0.5:0.5, and fully mixing by magnetic stirring for 4-8 hours; S8. The mixed slurry is coated and vacuum dried, and finally a half-cell is fabricated and the electrochemical performance is tested.

2. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation according to claim 1, Features: In step S3, the ratio of nFe / nP is 0.96, and the ratio of nLi / nFe is 1.

034.

3. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation according to claim 2, Features: In step S3, the water-soluble starch is 4.25-4.5 g, the nano-TiO 2 0.32g, LiFePO 4 The precursor is 36 g, dissolved in 100 mL of deionized water.

4. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation according to claim 1, Features: In step S4, the sanding time is 90 minutes.

5. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation according to claim 4, Features: In step S4, the solid-liquid ratio is controlled at 8%.

6. A method for preparing modified lithium iron phosphate by carbon-coated metal doping and positive electrode lithium supplementation according to claim 1, Features: In step S6, the temperature is increased to 150°C at a rate of 6°C / min and kept at that temperature for 1 hour, then increased to 450°C / min at a rate of 5°C / min and kept at that temperature for 1 hour, and finally increased to 675°C-700°C at a rate of 2.5°C / min and kept at that temperature for 6 hours.

7. A method for preparing lithium carbonate and recovering aluminum and phosphorus from a pyroxenite according to claim 1, Features: In step S7, the magnetic stirring time is 8 hours.

Citation Information

Cited By

  • Halogenated electrolyte modified low-impedance positive electrode as well as preparation process and application thereof

    CN120895593A

  • Method for preparing and modifying lithium iron phosphate positive electrode material by combining solid phase method and liquid phase method

    CN121426076A